Investigation of critical factors on corporate entrepreneurship: Rethinking the organization culture - Kim, Ji Yeon; Park, Min Jae (Journal of Entrepreneurship in Emerging Economies, 2021)
Purpose: The purpose of this study is to investigate critical factors needed for an internal environment conducive to entrepreneurial activity. Also, this study aims to suggest improved measurement items that can be applied to national corporations in the national management environment where is much interested in the implementation of corporate entrepreneurship. Design/methodology/approach: In particular, by using the corporate entrepreneurship assessment instrument (CEAI) and through the Delphi and analytical hierarchy process (AHP) surveys on the group of corporate entrepreneurship experts, a comparative analysis among the emergent four kinds of types is deducted with main internal environmental factors of corporate entrepreneurship activities in South Korea. Findings: This study contributes to the decision-making of many organizations about new business directions and success factors to gain new growth opportunities with corporate entrepreneurship activities according to each of their own internal environment status. As a result of the AHP analysis on the opportunist type, work discretion was revealed as the most significant factor. Furthermore, the avoiding identical work approach/steps, the subjective work assessment and the opportunities to practice one’s own style were all recognized as crucial enough to occupy the top to fourth place in the overall importance priority. Originality/value: Academically, the local organizational environmental critical factors based on an existing CEAI were issued by allowing the AHP survey with specific scenarios per corporate entrepreneurship activity. This can be applied through various means to benefit many organizations looking for continuous growth and innovation based on corporate entrepreneurship.
Keywords: AHP; Corporate entrepreneurship; Delphi; Emergent types; Entrepreneurial activities; Organization culture